Relative age effect across the talent identification process of youth female soccer players in the United States: Influence of birth year, position, biological maturation, and skill level - Finnegan, L.; van Rijbroek, M.; Oliva-Lozano, J. M.; Cost, R.; Andrew, M. (Biology of Sport, 2024)
The aims of the study were to examine the relative age effect (RAE) in youth female soccer players in the United States (US) and the influence of birth year, playing position, estimated maturation and skill ratings. The sample consisted of 3,364 youth female soccer players who were active in the 2021-2022 US soccer season across three main stages of the talent identification (TID) process for Youth National Team (YNT) players (i.e., Club, TID Center, and YNT). A prevalent RAE for players born in Q1 was present in the full sample. A significant prevalence for Q1 players were identified for both Club and TID Center, but not YNT. A significant RAE prevalence for Q1 players was identified for most of the age groups from U13-U18 at Club (except U18) and TID Center (except U17). Significant RAEs prevalence for players born in Q1 were found in Goalkeepers, Center Backs, Midfielders, and Center Forwards at Club and TID Center (except Wide Forwards). The data identified a consistent RAE prevalence for Q1 players in early and on-time-maturers across all levels. An even birthdate spread was evident in YNT with a prevalence for Q4 players and a higher percentage of late maturers than elsewhere in the TID process. Results reinforce evidence indicating RAEs still exist in soccer, yet show for the first time within a youth female soccer TID process, the influence of contextual factors on the prevalence of RAE. This information can be used to advance TID and development across the US soccer landscape.